Laboratory Evolution of GH11 Endoxylanase Through DNA Shuffling: Effects of Distal Residue Substitution on Catalytic Activity and Active Site Architecture - Liu, Ming-Qi; Li, Jia-Yi; Rehman, Ashfaq Ur; Xu, Xin; Gu, Zhu-Jun; Wu, Ruo-Chen (Frontiers in Bioengineering and Biotechnology, 2019)
Endoxylanase with high specific activity, thermostability, and broad pH adaptability is in huge demand. The mutant library of GH11 endoxylanase was constructed via DNA shuffling by using the catalytic domain of Bacillus amyloliquefaciens xylanase A (BaxA) and Thermomonospora fusca TF xylanase A (TfxA) as parents. A total of 2250 colonies were collected and 756 of them were sequenced. Three novel mutants (DS153: N29S, DS241: S31R and DS428: I51V) were identified and characterized in detail. For these mutants, three residues of BaxA were substituted by the corresponding one of TfxA_CD. The specific activity of DS153, DS241, and DS428 in the optimal condition was 4.54, 4.35, and 3.9 times compared with the recombinant BaxA (reBaxA), respectively. The optimum temperature of the three mutants was 50 °C. The optimum pH for DS153, DS241, and DS428 was 6.0, 7.0 and 6.0, respectively. The catalytic efficiency of DS153, DS241 and DS428 enhanced as well, while their sensitivity to recombinant rice xylanase inhibitor (RIXI) was lower than that of reBaxA. Three mutants have identical hydrolytic function as reBaxA, which released xylobiose–xylopentaose from oat spelt, birchwood, and beechwood xylan. Furthermore, molecular dynamics simulations were performed on BaxA and three mutants to explore the precise impact of gain-of-function on xylanase activity. The tertiary structure of BaxA was not altered under the substitution of distal residues (N29S, S31R, and I51V); it induced slightly changes in active site architecture. The distal impact rescued the BaxA from native conformation (“closed state”) through weakening interactions between “gate” residues (R112, N35 in DS241 and DS428; W9, P116 in DS153) and active site residues (E78, E172, Y69, and Y80), favoring conformations with an “open state” and providing improved activity. The current findings would provide a better and more in-depth understanding of how distal single residue substitution improved the catalytic activity of xylanase at the atomic level.